Current treatment methods for long occlusions of the femoropopliteal segment in patients with intermittent claudication: Minireview - Fialová, Jana; Utíkal, Petr; Bachleda, Petr; Köcher, Martin; Černá, Marie; Vomáčková, Katherine (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
UNLABELLED: Backround. Intermittent claudication is a classic symptom of peripheral arterial disease. It is mainly treated conservatively but if this fails, a form of revascularization is indicated. The revascularization in chronic occlusion of femoropopliteal region is currently performed by two basic methods: the standard method of surgical bypass and the newer miniinvasive alternative represented by the endovascular method. The treatment of patients with solely claudication and long occlusion of femoropopliteal region remains controversial. The aim of this minireview was to determine whether surgical bypass is still the best method of choice in a time of endovascular techniques. METHODS: A MEDLINE search for original and review articles using key terms, intermittent claudication and long femoropopliteal oclusion. RESULTS AND CONCLUSION: No ideal treatment for long occlusions of the femoropopliteal segment has been established to date. It is clear that the role of endovascular techniques in the treatment of SFA occlusions is increasing. It remains that, lower risk patients with claudication should be examined to assess the quality of veins suitable for revascularization and bypass should be selected as the first method of choice.
Keywords: Endovascular Procedures; cévní protézy; Vascular Surgical Procedures; Blood Vessel Prosthesis; Intermittent Claudication; Femoral Artery; intermitentní klaudikace; reperfuze; Blood Vessel Prosthesis Implantation; cévy - implantace protéz; Humans; Popliteal Artery; arteria femoralis; Reperfusion; arteria poplitea; výkony cévní chirurgie; lidé; endovaskulární výkony